#naovaitercopa: manifestações, Copa do Mundo e as eleições de 2014 - Romao, Wagner de Melo [UNESP] (My University, 2014)
The article aims to recover the manifestations process of June 2013, in an attempt to understand the elements, which characterized it. It is intended to indicate how and why the main political consequences generated by the manifestations became its own possibility of a rematch in June 2014, during the hosting of the World Cup, organized by FIFA and the Brazilian government. It is suggested which may be the nature and extent of its impacts over the general election in this year. It is argued that the key issue is the ability of the State, the governments and their police in dealing with manifestations that have, relatively, new, persuasive, and violent ideas.

O artigo busca recuperar o processo das manifestações de junho de 2013, na tentativa de compreender os elementos que a caracterizaram. Pretende-se indicar como e porque a principal consequência política gerada pelas manifestações tornou-se a própria possibilidade de sua reedição, em junho de 2014, durante a realização da Copa do Mundo de Futebol, organizada pela FIFA e pelo governo brasileiro. Indica-se qual poderá ser a natureza e amplitude dos impactos de uma eventual nova onda de manifestações sobre as eleições gerais nesse ano. Defende-se que o elemento chave da questão está na capacidade do Estado, dos governos e de sua polícia em lidar com manifestações com repertórios relativamente novos e mais incisivos e violentos.
#naovaitercopa: manifestations, World Cup and 2014 elections
Keywords: Manifestations of June 2013; 2014 Elections; Police; Manifestações de junho de 2013; Eleições 2014; Polícia